PENGARUH CORPORATE GOVERNANCE DAN KEBIJAKAN PENDANAAN TERHADAP KINERJA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Marselino Wau (Jurnal Ekonomi dan Bisnis Nias Selatan, 2021)
The performance of manufacturing companies where corporate governance with indicators of the number of commissioners and independent commissioners, while funding policies with indicators of Debt Equity Ratio and performance dependent variable with indicators of Return On Assets (ROA). The sample used in this study were 143 Manufacturing companies listed on the Indonesia Stock Exchange that publish Annual Reports for 2015-2016. The method used in this research is the multiple regression method. The results of this study indicate that corporate governance affects the company's performance with a significant value of less than 0.05 and also that funding policies affect the company's performance.